Sylvia Plath images of life in a poet of death - Mather, Mary Lynn (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1992)
On a creative and a personal level, Sylvia Plath seems to have been fascinated by the relationship between life and death. Her work reflects an ongoing preoccupation with duality and a sense of tension between two opposing forces suffuses virtually every poem she wrote in the period from 1956 to early 1963. Because her attitude to both life and death is deeply ambivalent, Plath's poetry rests on a strong awareness of conflict and her art is characterized by a continual pull between extremes. This thesis is an examination of how she uses images of life in poems that ostensibly deal with death.While Plath draws on the events of her own life for her poetic material, she also converts her personal experiences into a universal myth. She was familiar with Robert Graves's eclectic study of the pagan nature deity, The White Goddess, and she seems to have incorporated part of his symbolism into her own code of images. In particular, she adopts Graves's triple goddess of nature as one of the dominant figures in her created world, for the White Goddess is associated with life and death alike.Plath's dichotomy of life and death works on different planes. Firstly, she frequently envisages the self as divided and the opposition between life and death takes on the dimensions of an internal psychological war. Secondly, she extends the battle between life and death to the creative sphere. Thirdly, she explores the idea of life as a journey from birth to death. The White Goddess is linked with the three natural realms of earth, sky and underworld. And Plath relies largely on seasonal, lunar and chthonic images in her poetry. Furthermore, the three colours of the goddess - white , red and black - are the dominant hues of her poetry.
Keywords: Plath, Sylvia; Plath, Sylvia -- Criticism and interpretation